Efficacy of everolimus plus hormonal treatment after cyclin-dependent kinase inhibitor; real-life experience, A TOG study - Beypinar, Ismail; Demir, Hacer; Yaslikaya, Sendag; Koseci, Tolga; Demir, Bilgin; Colak, Gokhan; Karacin, Cengiz (Springer, 2024)
Purpose In advanced breast cancer, endocrine therapy is preferred in the absence of visceral crisis. Cyclin-dependent kinase inhibitors (CDKi) are the gold standards. The selection of subsequent treatments after CDKi treatment is still controversial, and the efficacy of everolimus (EVE) combinations is unknown. In this study, we aimed to investigate the efficacy of EVE after CDKi administration in real-life experiences. Method The study received data from 208 patients from 26 cancer centers. Demographic and histologic features, diagnosis, progression, last visit dates, and toxicities were recorded. This study was a retrospective case series. Results One hundred and seven patients received palbociclib, while 101 patients received ribociclib as a CDKi. The overall response and disease control rates of EVE combinations were 60% and 88%, respectively. In univariate analysis, the absence of liver metastasis, age > 40 years, better type of response, and immediate treatment after CDKi were related to increased progression-free survival. Liver metastasis and response type were significantly associated with overall survival. In the multivariate analysis, response remained significant in terms of progression-free survival, while response type, liver metastatic disease, and hematologic toxicity were prognostic in terms of overall survival. Conclusion This study provides evidence of the benefits of EVE combinations after CDKi treatment. EVE combinations may be more appropriate for patients with non-liver metastasis, and the first treatment response shows the benefit of treatment. In addition, immediate treatment after CDKi treatment is more beneficial than later lines of treatment.
Keywords: Everolimus; Breast cancer; Cyclin-dependent Kinase Inhibitors; Palbociclib; Ribociclib; Life experience